Remodeling of Actin Cytoskeleton in Mouse Periosteal Cells under Mechanical Loading Induces Periosteal Cell Proliferation during Bone Formation - Sakai, Daisuke; Kii, Isao; Nakagawa, Kazuki; Matsumoto, Hiroko N.; Takahashi, Masateru; Yoshida, Suguru; Hosoya, Takamitsu; Takakuda, Kazuo; Kudo, Akira (PLOS ONE, 2011)
Background The adaptive nature of bone formation under mechanical loading is well known; however, the molecular and cellular mechanisms in vivo of mechanical loading in bone formation are not fully understood. To investigate both mechanisms at the early response against mechanotransduction in vivo, we employed a noninvasive 3-point bone bending method for mouse tibiae. It is important to investigate periosteal woven bone formation to elucidate the adaptive nature against mechanical stress. We hypothesize that cell morphological alteration at the early stage of mechanical loading is essential for bone formation in vivo. Principal Findings We found the significant bone formation on the bone surface subjected to change of the stress toward compression by this method. The histological analysis revealed the proliferation of periosteal cells, and we successively observed the appearance of ALP-positive osteoblasts and increase of mature BMP-2, resulting in woven bone formation in the hypertrophic area. To investigate the mechanism underlying the response to mechanical loading at the molecular level, we established an in-situ immunofluorescence imaging method to visualize molecules in these periosteal cells, and with it examined their cytoskeletal actin and nuclei and the extracellular matrix proteins produced by them. The results demonstrated that the actin cytoskeleton of the periosteal cells was disorganized, and the shapes of their nuclei were drastically changed, under the mechanical loading. Moreover, the disorganized actin cytoskeleton was reorganized after release from the load. Further, inhibition of onset of the actin remodeling blocked the proliferation of the periosteal cells. Conclusions These results suggest that the structural change in cell shape via disorganization and remodeling of the actin cytoskeleton played an important role in the mechanical loading-dependent proliferation of cells in the periosteum during bone formation.